2000
DOI: 10.1007/bf02439274
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of primary humoral immune response in mice with cytostatic disease

Abstract: Single intraperitoneal injection of cyclophosphamide in a maximum permissible dose (250 mg/kg) followed by immunization wih thymus-dependent antigen (sheep erythrocytes) markedly suppressed the formation of antibody-producing cells in the spleen, especially at early stages of cytostatic disease, and delayed the synthesis of specific antibodies in male CBA/CaLac mice. Platidiam (cisplatin) injected in comparable doses 4 days before immunization practically did not suppress the formation of antibody-producing ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Many authors quoted doses less than 250-400 mg/kg b.wt. of this drug as sub-lethal and effective to induce immunosuppression (Artyma et al, 2003;Davis and Kuttan, 1998;Masnaya and Ratner, 2000). The observations of this study suggest that IG is able to augment the therapeutic effect of the alkylating agent CYP at sublethal doses in the DLA treated mice, at the same time, inhibiting its adverse effects.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Many authors quoted doses less than 250-400 mg/kg b.wt. of this drug as sub-lethal and effective to induce immunosuppression (Artyma et al, 2003;Davis and Kuttan, 1998;Masnaya and Ratner, 2000). The observations of this study suggest that IG is able to augment the therapeutic effect of the alkylating agent CYP at sublethal doses in the DLA treated mice, at the same time, inhibiting its adverse effects.…”
Section: Discussionmentioning
confidence: 75%
“…CYP (50 mg/kg b.wt., i.p. for 4 alternating days) was used as the standard reference drug as reported (Artyma et al, 2003;Davis and Kuttan, 1998;Masnaya and Ratner, 2000). On 7th, 14th and 21st days, animals were sacrificed to determine the tumor volume.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…While cellular multiplication induced by concanavalin A is commonly used to detect T lymphocyte immunity in vitro, the LPS-induced activation of B cells and subsequent immunoglobulin synthesis reflect B lymphocyte immunity (Quakyi et al, 1997). Previous reports have shown that cyclophosphamide suppresses both humoral and cellular immune responses (Balow et al, 1975;Rondinone et al, 1983;Morato et al, 1996;Masnaya and Ratner, 2000). Indeed, a single dose of cyclophosphamide (200 mg/kg) inhibited the proliferative response to both B and T cells (Quakyi et al, 1997).…”
Section: Discussionmentioning
confidence: 93%
“…Cyclophosphamide (CTX) (50 mg/kg b.wt., i.p.) was used as the standard reference drug as reported [810] for DLA and 5-FU (20 mg/kg b.wt., i.p.) for EAC was used as the standard reference drug [11].…”
Section: Methodsmentioning
confidence: 99%